New Approaches to Multi-functional Soft Materials - (:unkn) unknown (My University, 2018)
Soft robotics is a relatively new, but fast-developing field of science and technology that utilizes soft materials such as polymers in their body structure. Despite significant progress in soft robotic devices, robots that can sense their environments are still very rare. Although some soft robots have exhibited sensing capabilities, they still have not demonstrated synergistic coupling of sensing and actuation. From our perspective, this type of coupling may take us one step closer to fabricate soft robots with autonomous feedback dynamics. In this work, we present new approaches to soft robotic devices, which are fabricated from responsive soft materials and are able to exhibit synergistic coupling of structural color-based sensing and actuation in response to environmental stimuli. Cephalopods, such as cuttlefish, are excellent models of coupled sensing and actuation. They demonstrate remarkable adaptability to the coloration and texture of their surroundings by modulating their skin color and surface morphology simultaneously and reversibly, for adaptive camouflage and signal communication. Inspired by this unique feature of cuttlefish skins, we present a general approach to remote-controlled, smart films that undergo simultaneous changes of surface color and morphology upon infrared (IR) actuation. The smart film has a reconfigurable laminated structure that comprises an IR-responsive nanocomposite actuator layer and a mechanochromic elastomeric photonic crystal layer. Upon global or localized IR irradiation, the actuator layer exhibits fast, large, and reversible strain in the irradiated region, which causes a synergistically coupled change in the shape of the laminated film and color of the mechanochromic elastomeric photonic crystal layer in the same region. Complex 3D shapes, such as bending and twisting deformations, can be created under IR irradiation, by modulating the strain direction in the actuator layer of the laminated film. Finally, the laminated film has been used in a remote-controlled inchworm walker that can directly couple a color-changing skin with the robotic movements. Such IR-actuated, reconfigurable films could enable new functions in soft robots and wearable devices. A crucial aspect of soft robotics is the sensing capabilities of the robot. Colorimetric sensing based on structural colors, mostly photonic crystals, has been explored. A major challenge is overcoming the problems of limited scalability and time-consuming fabrication process, which affect the real-world applications of photonic crystals. Herein, we have developed a new scalable and affordable platform technology for fabrication of stimuli-responsive, interference colored films. Our system is composed of a thin film of a transparent polymer deposited on a metal-coated substrate. The facile fabrication process allows us to create full spectrum of interference colors on both rigid and soft substrates by simply adjusting the thickness of the polymer layer. Furthermore, our films have been used as colorimetric sensors which undergo fast and reversible change of surface color upon changes in environmental humidity. Such polymer-based, responsive interference coloration could empower colorimetric sensing of various environmental stimuli (e.g. humidity, chemicals, heat, and mechanical forces), which could enable a wide range of applications.
Keywords: Actuation; Liquid crystalline elastomers; Photonic crystals; Responsive interference coloration; Sensing; Soft robotics